Off-Campus Policy on The Social and Academic Activities of Undergraduates in Nigerian Tertiary Institution - Joseph Kayode ADEYEMI (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2022)
The paper examined the challenges of undergraduate’s students on off-campus life on their social life and academic performance. It is a form of descriptive design that uses a representative sample to collect data. The population consist of all undergraduate students in all the six faculties of Adekunle Ajasin University, Akungba-Akoko. A simple random sampling technique was used to select 200 students, the instrument for data collection was self-constructed questionnaire titled “off-campus, social and academic life of undergraduates’’ on four-point likert scale. The face and content validity of the instrument was ascertained by the researchers. Test-retest technique was used by the researcher, Pearson product movement correlation was used to determine the correlation coefficient which was 0.76. Three hypotheses were formulated to guide the study. The hypotheses were tested using Pearson Product Moment Correlation analysis. The result indicated that there was a significant relationship between off-campus life and academic activities of undergraduate students. The result also showed that there was a significant relationship between off-campus life and academic activities of undergraduate students, and finally the result revealed that there is a significant relationship between off-campus life and academic activities of undergraduate students. It was suggested that The Management of the institution should monitor the activities of students living off-campus.